PERAN SEKOLAH MENGATASI MASALAH PERILAKU ANAK MELALUI BIMBINGAN KELOMPOK BERBASIS BUDAYA DI DESA GUNUNGSARI - Bunga Aprilia; Lida Maulida; Naurah Nazifah; Febri Dahlia; Aceng Akhmad Munanzdar Alkafi Billah (Fakultas Tarbiyah dan Keguruan, 2025)
Behavioral problems of elementary school students, such as low discipline, conflicts between friends, and difficulty controlling emotions, are challenges that can hinder the achievement of learning objectives and character building. Schools as formal educational institutions have a strategic role in overcoming these problems through the provision of appropriate counseling guidance services. This community service activity aims to describe the role of schools in overcoming children's behavior problems through culture based group guidance at SDN Gunungsari, Tangerang Regency, in 2024. The implementation method consists of preparation, planning, implementation, evaluation, and follow-up stages. The subjects were 25 students in grades IV and V who were selected based on the results of classroom teacher observations and behavior checklist instruments. The intervention was conducted through six group guidance sessions using the traditional game congklak and reflective discussions based on local cultural values. The results showed a significant decrease in problem behavior, especially in the aspects of discipline, cooperation skills, and emotional control. Classroom teachers acted as facilitators and counselors who accompanied students throughout the process, and provided positive value reinforcement in daily interactions. In conclusion, culture-based group guidance is effective in helping schools shape students' positive behavior while instilling local wisdom values.